2020
DOI: 10.3389/fgene.2020.00678
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlation for Predicting Cochlear Implant Outcome: Current Challenges and Opportunities

Abstract: The use and utility of cochlear implantation has rapidly increased in recent years as technological advances in the field have expanded both the efficacy and eligible patient population for implantation. This review aims to serve as a general overview of the most common hearing disorders that have favorable auditory outcomes with cochlear implants (CI). Hearing loss in children caused by congenital cytomegalovirus infection, syndromic conditions including Pendred Syndrome, and non-syndromic genetic conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 164 publications
(240 reference statements)
1
13
0
1
Order By: Relevance
“…Spiral ganglion neurons are necessary to transmit a CI-initiated electrical stimulation to the brainstem. Nevertheless, two recent reviews on this subject point to individuals with auditory neuropathy spectrum disorders (ANSD) who do benefit from cochlear implants (Eshraghi et al 2020;Shearer and Hansen 2019). Benefit from a CI depends on the site and magnitude of the physiological lesion.…”
Section: Rna-seq Of Perrault Syndrome Genes Demonstrates Prominent Expression In Spiral Ganglion Neuronsmentioning
confidence: 99%
“…Spiral ganglion neurons are necessary to transmit a CI-initiated electrical stimulation to the brainstem. Nevertheless, two recent reviews on this subject point to individuals with auditory neuropathy spectrum disorders (ANSD) who do benefit from cochlear implants (Eshraghi et al 2020;Shearer and Hansen 2019). Benefit from a CI depends on the site and magnitude of the physiological lesion.…”
Section: Rna-seq Of Perrault Syndrome Genes Demonstrates Prominent Expression In Spiral Ganglion Neuronsmentioning
confidence: 99%
“…Accumulating evidence reveals that CI outcomes correlate closely with the etiologies of pediatric SNHL [ 12 , 13 , 14 , 15 ]. We recently demonstrated that comprehensive history-taking, genetic examinations, and imaging studies were useful in addressing the etiological heterogeneity of pediatric ANSD and could help obtain information regarding the causes of ANSD in 75% of the patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that patients with DFNB2 have been subsequently investigated and diagnosed for mild RP. Nevertheless, “age at surgery” is the most important prognostic factor [ 58 , 59 , 60 ]. Ineligible cases till surgery or poor outcomes of CIs may benefit from tactile and sign language [ 61 ].…”
Section: Genetics Of Ushmentioning
confidence: 99%